2015
DOI: 10.1177/0960327115579430
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear changes in oral mucosa of alcoholics and crack cocaine users

Abstract: The effects of drugs of abuse on oral mucosa are only partly understood. The aims of the present study were to: (1) evaluate the frequency of nuclear changes in normal-appearing oral mucosa of alcoholics and crack cocaine users and (2) assess their association with cell proliferation rate. Oral smears were obtained from the border of the tongue and floor of the mouth of 26 crack cocaine users (24 males and 2 females), 29 alcoholics (17 males and 12 females), and 35 controls (17 males and 18 females). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 48 publications
(93 reference statements)
2
24
0
Order By: Relevance
“…The results showed that the frequency of micronuclei and karyorrhexis increased significantly. Our results corroborate the findings of some authors, such as Webber et al and de Freitas et al 18,25 These authors observed a frequency of micronuclei and nuclear buds was significantly increased in peripheral blood lymphocytes and oral mucosa. In 2014, das Graças Alonso de Oliveira et al 26 have investigated the frequency of micronucleus in oral mucosa of crack cocaine users too.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that the frequency of micronuclei and karyorrhexis increased significantly. Our results corroborate the findings of some authors, such as Webber et al and de Freitas et al 18,25 These authors observed a frequency of micronuclei and nuclear buds was significantly increased in peripheral blood lymphocytes and oral mucosa. In 2014, das Graças Alonso de Oliveira et al 26 have investigated the frequency of micronucleus in oral mucosa of crack cocaine users too.…”
Section: Discussionsupporting
confidence: 93%
“…It can be repeated several times for the prevention and monitoring of individuals at risk for cancer, such as: chronic users of alcohol, smoking and / or other mutagenic substances. [15][16][17][18] The presence of micronuclei in exfoliated cells of oral mucosa reflects genotoxic events that occurred in cells that were in the basal layer of the epithelium 1-3 weeks before getting the smear. 13 Until the present date, there are few reports in the literature on the possible genotoxic and cytotoxic effects of crack that is often used with other drugs, such as cigarettes and alcohol (carcinogens).…”
Section: -14mentioning
confidence: 99%
“…With the introduction of quantitative techniques, oral cytology has become an important preventive exam for monitoring the oral mucosa exposed to carcinogens [2][3][4][5][6] . From these studies, it became apparent the individual nature of this type of evaluation, suggesting that some individuals are more susceptible than others to oral cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…Both methods of sample collection are inexpensive, facile, and non-invasive. [19][20][21] Hence, salivary nitric oxide and the comet assay of buccal cells optimally met all of the above requirements.…”
Section: Figurementioning
confidence: 95%